Menakar Peran Strategis Kesehatan Reproduksi Remaja dan Pendewasaan Usia Perkawinan dalam Mencapai Bonus Demografi - Yuniarti . (Pena Medika Jurnal Kesehatan, 2013)
Background : Indonesia entering a new phase of population development by achieving demography bonus by the year 2015. Demography bonus refers to ratio between productive population (age 16-65 years old) and unproductive population is under 50 percent. A term of achieving demographic bonus is when Total Fertility Rate (TFR) at 2,1. But now Indonesia’s TFR at 2,6. There are two problems contributing to higher TFR, those unwanted pregnancies and early marriage.Methods : Thera are two main strategies overcome unwanted pregnancies and early marriage. First strategy: advance adolescent reproductive health. The campaigns of adolescent reproductive health implemented in real actions increasing awareness and motivating adolescent be able fulfilling of reproductive rights safely and healthy appropriate age development. The campaigns of adolescent reproductive health involving them to be role models. Second strategy : maturating marriage age upto 20 years old whenever its safely reproductive. Results : These study concluded the campaign of adolescent reproductive health implemented in youth friendly atmosphere according with the characterstics of adolescent. Information about adolescent health reproductive focuses on negative impacts of unwanted pregnancies, drugs and hiv aids. Maturating of marriage age able to decline maternal mortality lower and decreasing TFR onto ideal number. The higher TFR refers to higher early marriage age, lower education and economics level. Adolescent health reproductive and maturating marriage age have strategic roles to lower TFR by number of 2,1.  This study suggests :  delaying pregnancy until reaching age 20 years old for early marriage that had been accoured.  Adolescent health reproductive implemented in inclusion and integrated with education institution (school and university/higher education) such as adolescent red cross, scout, information and counseling center for students. Other suggestion is building adolescent’s self esteem positively by involving them for driving forces promotion of adolescent health reproductive. Key words : Strategic Roles, Adolescent Reproductive Health, Marriage Age Maturation, Demography Bonus